Partisipasi Penduduk Asli Kaili dan Etnis Bugis dalam Pelestarian Ritual Kupatan Etnis Jawa - Rahmadani, Devi; Marzuki, Muhammad; Bakari, Yulianti; Muzakkir, Abd. Kahar (SIGn Journal of Social Science, 2023)
This research aims to understand the process of the Kupatan ritual by the Java ethnicity and the participation forms of the Kaili indigenous people and Bugis ethnicity in the Kupatan ritual in Bahagia Village. This research uses an ethnographic analysis. Ethnographic analysis is an approach that begins with field facts, analyzes them based on cultural theories and relevant arguments to explore the cultural situation of the community, and ultimately yields a conclusion. The results show that the participation of the Kaili indigenous people and the Bugis ethnicity in the preservation of the Kupatan ritual by the Java ethnicity in Bahagia Village demonstrates impressive cultural collaboration, manifested through various processes from the opening, sermon and joint prayer, handshaking, to ngambeng or communal eating. This participation, which occurs in voluntary, spontaneous, and habitual forms, marks deep social and cultural integration among the three ethnic groups. Therefore, it is recommended that the Department of Education and Culture of Sigi Regency enhance support for documenting and promoting the Kupatan ritual as a cultural heritage that enriches local diversity. The residents of Bahagia Village are advised to continue maintaining and expanding participation in the Kupatan ritual, as part of an inclusive cultural preservation effort. The Java ethnicity, Kaili indigenous people, and Bugis ethnicity are encouraged to continue fostering inter-ethnic cooperation and dialogue in celebrating the Kupatan ritual by organizing joint activities to enhance understanding and appreciation of each other’s cultures. It will strengthen inter-ethnic collaboration and harmony and ensure the sustainability of the Kupatan ritual as a symbol of unity and diversity in Bahagia Village.